EFEKTIVITAS PENYELENGGARAAN PROGRAM DIKLAT DARING BAGI GURU KEJURUAN DI BBPPMPV BMTI CIMAHI - Abdullah Abdullah (Jurnal Tata Kelola Pendidikan, 2021)
This study aims to describe the effectiveness of the implementation of the Effectiveness of the Online Education and Training Program for Vocational Teachers held at the Center for the Development of Quality Assurance for Vocational Education in the Mechanical and Industrial Engineering Sector (BBPPMPV BMTI) Cimahi. The research method used in this research is descriptive research method with a qualitative approach. Data collection techniques through interviews, observation and documentation studies. Check the validity of the data is done by triangulation technique. The results showed that the implementation of the Online Training Program for Vocational Teachers at BBPMPPV BMTI Cimahi had been running effectively. This is evidenced by the achievement of objectives in each stage of implementation, namely planning, implementation, and evaluation. : (1) The online training program planning process: there is a careful planning and can be seen from the online training guide, adequate facilities and infrastructure but need to be adjusted for online training, training costs are available, training participants are in accordance with the criteria, education and training personnel are in accordance with the requirements and conditions. (2) The process of implementing the Online Education and Training program: preparation for the implementation of the training through preparation meetings/technical guidance, the availability of facilities for the implementation of online training, and an interactive learning process. (3) Evaluation of the online education and training program: adjustment of the evaluation instrument, the purpose of the evaluation is achieved by the existence of a report on the implementation of the training and submitted at the close of the education and training program.